Workplace Discrimination and Job Satisfaction in Nepalese Organizations - Thapa, Makshindra; Niraula, Damodar (The Batuk, 2024)
Workplace discrimination is the state of unfair treatment to employees based on the factors irrelevant to their job performance. It affects individuals’ job efficiency, their lives and the organization in whole. This study has been carried out to examine the relationship of workplace discrimination with job satisfaction of employees in Nepalese organizations. Primary data were collected by administering a set of questionnaires that comprise 5-point Likert Scale statements on job satisfaction and the different forms of discrimination. Respondents were selected using convenient and snowball sampling method. Response from 196 workers collected through google form was analyzed on SPSS. The descriptive results show that prejudice against individuals on the basis of gender, religion, and nepotism is moderate. The other forms of discrimination, based on age, race, and favoritism, have been determined to be normal. Pearson's association between workplace discrimination based on gender, religion, nepotism, and job satisfaction revealed a statistically significant negative correlation. There was no significant correlation found between work satisfaction and age, race, or favoritism. The findings offer insightful information and inspiration for future studies and initiatives focused on understanding and addressing discrimination at the workplace.